2011
DOI: 10.4300/jgme-d-11-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Letters of Recommendation in Predicting Resident Success: Can the ACGME Competencies Help?

Abstract: LORs can provide useful clues to differentiate between students who are likely to become the least versus the most successful residency program graduates. Greater usage of the ACGME core competencies within LORs may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…These results correspond the to the high value that is placed on recommendation letters by residency program directors in the medical field 17,18 . One study demonstrated that letters of recommendation written for students applying to residency programs may be useful in predicting resident performance at the extremes 19 . Further, Wagoner and Suriano 20 showed that >90% of the directors required ≥2 letters of recommendation before considering a student for interview.…”
Section: Discussionsupporting
confidence: 52%
“…These results correspond the to the high value that is placed on recommendation letters by residency program directors in the medical field 17,18 . One study demonstrated that letters of recommendation written for students applying to residency programs may be useful in predicting resident performance at the extremes 19 . Further, Wagoner and Suriano 20 showed that >90% of the directors required ≥2 letters of recommendation before considering a student for interview.…”
Section: Discussionsupporting
confidence: 52%
“…[1][2][3][4][5][6][7][8][9] Letters of recommendation (LOR) are widely considered a core component of the application for residency placement, yet studies of their predictive value are limited. [10][11][12][13][14][15][16] Although many fields rely on traditional narrative LORs (NLORs), emergency medicine (EM) adopted a Standardized LOR (SLOR). The Council of Emergency Medicine Residency Directors (CORD) SLOR has become the primary tool used by EM faculty to evaluate candidates applying for residency.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other studies have called into question the specificity and predictive power of letters of recommendation 19 and have questioned whether their usefulness may be limited to differentiating only between the best and the worst of applicants. 20 Indeed, less-qualified candidates also need to find someone willing to write a letter that at the very least will not hurt them. To that end, as Richard Friedman suggested in his 1983 New England Journal of Medicine article 'Fantasy Land', letters of recommendation can become exaggerated or vague, nearly to the point of uselessness because we have created a convention in which everyone ranges from 'above average' to 'superior'.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent survey of plastic surgery programme directors, the majority felt that letters of recommendation did not provide a useful or realistic way of comparing candidates, a finding echoed in general surgery . Other studies have called into question the specificity and predictive power of letters of recommendation and have questioned whether their usefulness may be limited to differentiating only between the best and the worst of applicants . Indeed, less‐qualified candidates also need to find someone willing to write a letter that at the very least will not hurt them.…”
Section: Introductionmentioning
confidence: 99%